El perdón estratégico: Una necesidad para vivir juntos (2020)
The present article addresses Strategic pardons, pardons which emerge in the transitional justice framework not only as a necessity to stop a military conflict but also as an imperative to help build peace within a particular social context affected by extreme violence. The objective of the article is to examine the strategic forgiveness in an ethical key and, from a hermeneutic reading, to demonstrate the need to live together to rebuild the social fabric and, to live humanly with all that can mean. © 2020, Universidad del Zulia. All rights reserved.